Evolving origin-of-transfer sequences on staphylococcal conjugative and mobilizable plasmids - Who's mimicking whom? - Yui Eto, K.; Kwong, S.M.; Labreck, P.T.; Crow, J.E.; Traore, D.A.K.; Parahitiyawa, N.; Fairhurst, H.M.; Merrell, D.S.; Firth, N.; Bond, C.S.; Ramsay, Josh (OXFORD UNIV PRESS, 2021)
In Staphylococcus aureus, most multiresistance plasmids lack conjugation or mobilization genes for horizontal transfer. However, most are mobilizable due to carriage of origin-of-transfer (oriT) sequences mimicking those of conjugative plasmids related to pWBG749. pWBG749-family plasmids have diverged to carry five distinct oriT subtypes and non-conjugative plasmids have been identified that contain mimics of each. The relaxasome accessory factor SmpO, encoded by each conjugative plasmid, determines specificity for its cognate oriT. Here we characterized the binding of SmpO proteins to each oriT. SmpO proteins predominantly formed tetramers in solution and bound 5'-GNNNNC-3' sites within each oriT. Four of the five SmpO proteins specifically bound their cognate oriT. An F7K substitution in pWBG749 SmpO switched oriT-binding specificity in vitro. In vivo, the F7K substitution reduced but did not abolish self-transfer of pWBG749. Notably, the substitution broadened the oriT subtypes that were mobilized. Thus, this substitution represents a potential evolutionary intermediate with promiscuous DNA-binding specificity that could facilitate a switch between oriT specificities. Phylogenetic analysis suggests pWBG749-family plasmids have switched oriT specificity more than once during evolution. We hypothesize the convergent evolution of oriT specificity in distinct branches of the pWBG749-family phylogeny reflects indirect selection pressure to mobilize plasmids carrying non-cognate oriT-mimics.